Dampak Liberalisasi Keuangan dan Perdagangan Internasional Terhadap Pertumbuhan Ekonomi Indonesia 1970-2002 - Rini Dwi Astuti (Universitas Islam Indonesia, 2005)
The objective of this study was to examine the empirical relationship between finan¬cial and international trade liberalisation and long-run growth by using bank credit to the private sector as an indicator of financial liberalisation, and export plus import values as an indicator of international trade liberalisation. It argues that these indicators have a clear advantage over economic growth in Indonesia during 1970-2002. This study applies the en¬dogenous growth model and error correction model. It explores the joint impact of both fi¬nancial and international trade liberalisation and the impact of investment in physical and human capital on the growth of real income. The main findings are as follows: First, in short run, the study finds its measure of international liberalisation, physical and human capital investment to have a significantly positive effect on the economic growth, and it measure of financial liberalisation has no significantly positive effect on the economic growth. Second, in long run, except human capital investment, it finds the impact of physical capital invest¬ment, financial and international trade liberalisation on economic growth to be consistent with long-run growth theory. Keywords: Endogenous Economic Growth; Financial and International Trade Liberalisa¬tion; Error Correction Model.